Building professional Android applications - (caron)Subonis, Tadas; Safari eBooks ([Place of publication not identified] : Packt, 2018)
"Develop a real-world app using modern persistence frameworks, advanced data structures, testing, and high-quality front-end development. Dive deep into Android development with practical hands-on examples to help you at each stage. Develop smart professional grade apps for the latest Android N version and become a pro Android developer. Unclog your development highway by utilizing the industry-standard best practices techniques"--Resource description page.
Title from title screen (viewed April 16, 2018).
Release date from resource description page (Safari, viewed April 16, 2018).
Presenter, Tadas (caron)Subonis.
Keywords: Android (Electronic resource); Application software -- Development; Mobile computing; Electronic books